AANALYSIS IN THE PRODUCTION OF SEEDBEDS AND THE MARKETING OF SEEDLINGS IN THE INFLUENCE AREA IN QUEVEDO CITY, LOS RIOS PROVINCE FOR THE ESTABLISHMENT OF TEAK PLANTATION (Tectona grandis L.F.) - Díaz Coronel, Teofilo Gorki (2010)
Many investors and producers of teak wood in Ecuador without supplies from seedlings produced by small plant nurseries no modern technology, and they have the largest supply of seedlings, the technification can be a limiting factor in normal development of commercial plantations which does not guarantee obtaining vigorous plantations, healthy and high-timber production. From this point of view is necessary to know the entire process of production of seedlings as well as the origin and seed management, production costs and marketing systems. The study was realized in the influence area of the Los Rios province, Ecuador, because in this province there are established most of teak plant nurseries that supply the demand on the ecuadorian. Coast and Amazon. It was found that small nursery owners occupy their own property, carry out field activities, supervisory or marketing, although not in large nurseries where the technician oversees the work. The large plant nursers use certified seed and nursers small plant use seeds harvested trees from in the locality. The costs of seedlings of small plant nursers and producer of stumps was 0.07 USD, and tech producer level and in vitro plantlets 0.19 USD. The best value is obtained at the level of stumps (36%) followed by the production of plantlets in vitro (31%). The demand for the coming years requires an amount of approximately three to four million of seedlings, while supply does not exceed two million and a half, there is an unsatisfied demand which must be satisfied by small producers, which becomes a challenge because must build strategic alliances to achieve competitive production costs.